Is there a difference in head posture and cervical spine movement in children with and without pediatric headache? - Budelmann, K.; von Piekartz, H.; Hall, Toby (Springer Berlin, 2013)
Pediatric headache is an increasingly reported phenomenon. Cervicogenic headache (CGH) is a subgroup of headache, but there is limited information about cervical spine physical examination signs in children with CGH. Therefore, a cross-sectional study was designed to investigate cervical spine physical examination signs including active range of motion (ROM), posture determined by the craniovertebral angle (CVA), and upper cervical ROM determined by the flexion–rotation test (FRT) in children aged between 6 and 12 years. An additional purpose was to determine the degree of pain provoked by the FRT. Thirty children (mean age 120.70 months [SD 15.14]) with features of CGH and 34 (mean age 125.38 months [13.14]) age-matched asymptomatic controls participated in the study. When compared to asymptomatic controls, symptomatic children had a significantly smaller CVA (p < 0.001), significantly less active ROM in all cardinal planes (p < 0.001), and significantly less ROM during the FRT (p < 0.001), especially towards the dominant headache side (p < 0.001).In addition, symptomatic subjects reported more pain during the FRT (p < 0.001) and there was a significant negative correlation (r=-0.758, p < 0.001) between the range recorded during the FRT towards the dominant headache side and FRT pain intensity score. This study found evidence of impaired function of the upper cervical spine in children with CGH and provides evidence of the clinical utility of the FRT when examining children with CGH.